Penerapan E-Tilang dalam Proses Pembayaran Denda E-Tilang di Unit Sat Lantas Polres Banyumas - Hendrian Syahputra (Police Studies Review, 2020)
This research was motivated by the high number of traffic violations but the people who chose to pay ticket fines through the Bank had begun to improve but in the last 3 months there were no payment tickets through banks due to the elimination of ticket ticket fines in the Banyumas police station, so that the E-ticket application in Banyumas police station is not optimal. The formulation of the problem in this thesis includes an Overview of Traffic Violations at the Banyumas Regional Police, How the implementation of the E-ticket in the payment of e-ticket fines in the unit of satjawali sat and the Banyumas Regional Police and what factors influence the implementation of E-ticketing in the payment process - said in the Turjawali unit sat then the Banyumas police station. As a knife analysis writer uses the theory of innovation success factors, Supervision Management Theory, the concept of procedures for prosecuting traffic violations, E-ticketing concepts and Police Technology Concepts, this thesis uses a qualitative approach with field research methods (field research). Technique of analyzing data through Data Reduction, Data Presentation and Withdrawal Conclusion. Based on the results of the research findings, the application of the E-ticket advocates payment of fines through banks with blue slips but in the application in the field in the last 3 months the E-ticketing system has not run optimally due to the revocation of the ticket penalty table by the court resulting in its application the E-ticket system is still in use but on the blue stamp slip Briva Number is not given and the offender must follow the trial and pay in court. In the discussion of the need to optimize the implementation of the system both in terms of innovation, communication channels, timeframes and social environment and provide several benefits for both the police and society, namely transparency, community, participation, accountability, justice and effective and efficient. In practice, there were still some shortcomings from the implementation of the E-ticket, namely the absence of a table of ticket fines between BRI banks and courts which resulted in the implementation of the E-ticket application not being optimally integrated. The factors that influence the successful implementation of E-tickets are leadership, management / organization, risk management, human capital and technology.